2014
DOI: 10.1142/s0192415x14500827
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhiza Injection on Pulmonary Heart Disease: A Systematic Review and Meta-Analysis

Abstract: Cor pulmonale (pulmonary heart disease) is a chronic progressive complicated disease for which treatment needs to be sustained all the time, creating a great financial burden on individuals and society. In order to improve the life quality of cor pulmonale patients and decrease the dosage and quantity of the routine treatment, in China, TCM is often administered to patients with cor pulmonale. The results of many clinical trials have indicated that Salvia miltiorrhiza and complex Salvia miltiorrhiza injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Furthermore, PPARγ agonists have found to reduce the production of ET‐1, which is the key signaling mechanism to induce PH. Pioglitazone can majorly reduce proliferation of PVSMC, PVR, and apoptosis in the experimental model of PH (Idris‐Khodja et al, ; Liu, Tian, et al, ; Sharma & Khanna, ). Recently, it has been demonstrated PPARγ agonist Rosiglitazone ameliorates endothelin‐1‐induced vasoconstriction of pulmonary arteries in the rat model (Liu, Tian, Huang, & Wang, ).…”
Section: Pharmacological Interventions and Their Molecular Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PPARγ agonists have found to reduce the production of ET‐1, which is the key signaling mechanism to induce PH. Pioglitazone can majorly reduce proliferation of PVSMC, PVR, and apoptosis in the experimental model of PH (Idris‐Khodja et al, ; Liu, Tian, et al, ; Sharma & Khanna, ). Recently, it has been demonstrated PPARγ agonist Rosiglitazone ameliorates endothelin‐1‐induced vasoconstriction of pulmonary arteries in the rat model (Liu, Tian, Huang, & Wang, ).…”
Section: Pharmacological Interventions and Their Molecular Aspectsmentioning
confidence: 99%
“…Herbal constituents of some phytomedicine are capable of improving the PH by modifying various participated signaling cascades. Resveratrol (Csiszar et al, ), Panax ginseng (Araliaceae) (Jiang et al, ), Genistein (Loganville) (Homma et al, ), Salvia Miltiorrhiza (Lamiaceae) (Liu, Huang et al, ), and Chinese herb Naofeikang (Han et al, ) have reported significant improvement in eNOS expression and simultaneous increase production of NO that can majorly knock down the endothelial dysfunction and associated PH (Table ). Indeed, Genistein can also decrease mean arterial pressure of pulmonary vessel and collagen deposition which is the major sign of PH (Homma et al, ).…”
Section: Pharmacological Interventions and Their Molecular Aspectsmentioning
confidence: 99%
“…Chronic cor pulmonale (CCP), a common type of heart disease, has become a rising major public problem that threatens people's health and quality of life around the world [1]. Although the term "cor pulmonale" is popular in the medical literature, there is presently no consensual definition [1][2][3]. World Health Organization (WHO) defined CCP as "hypertrophy of the right ventricle resulting from diseases affecting the function and/or structure of the lungs, and may further leading to heart failure" [4].…”
Section: Introductionmentioning
confidence: 99%
“…is the main clinical therapy for CCP [1]. However, it is universally acknowledged that long-time use of western medicine sometimes may cause drug resistance and toxic side effects, and therefore its clinical efficacy is still unsatisfactory [1,2]. Many researchers in China and some other Asian countries indicated that the combination of Chinese and Western medicine for CCP might be the potential trend of clinical treatment development in future [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Danshen injection, a Chinese traditional preparation from raw materials (roots and rhizoma of Salvia miltiorrhiza , Danshen), is widely used to treat hepatitis, menstrual disorders, menostasis and blood circulation diseases (Liu et al, ; Zhang et al, ; Cho et al, ; Shen, Yang, Sun, & Zheng, ; Wang, Zhao, Li, Gu, & Gou, ). In recent years, the water‐soluble components of Danshen have attracted increasing attention because of their effectiveness in improving the renal function of rats with adenine‐induced renal failure, and as antioxidants for their potential in removal of free radicals (Li et al, ; Guan et al, ).…”
Section: Introductionmentioning
confidence: 99%